Optimizing the interpretation of Clostridioides difficile two-step diagnostic algorithm results through antimicrobial stewardship - Christopher F. Lowe; Shayan Shakeraneh; Colin Lee; Azra Sharma; Victor Leung (Cambridge University Press, 2022)
Over a 4-year period, the antimicrobial stewardship team reviewed all positive (PCR+/Tox+) and indeterminate (PCR+/Tox−) cases with the most responsible physician for classification of patients as infection or colonization. Among 501 indeterminate samples, 213 (43%) were considered to be clinical infection, suggesting the need for ongoing clinical assessment of indeterminates.